2005
DOI: 10.1088/0741-3335/47/12b/s33
|View full text |Cite
|
Sign up to set email alerts
|

Production of radiatively cooled hypersonic plasma jets and links to astrophysical jets

Abstract: We present results of high energy density laboratory experiments on the production of supersonic radiatively cooled plasma jets with dimensionless parameters (Mach number ∼30, cooling parameter ∼1 and density contrast ρ j /ρ a ∼ 10) similar to those in young stellar objects jets. The jets are produced using two modifications of wire array Z-pinch driven by 1 MA, 250 ns current pulse of MAGPIE facility at Imperial College, London. In the first set of experiments the produced jets are purely hydrodynamic and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 40 publications
(52 reference statements)
2
49
0
Order By: Relevance
“…Lebedev 2005;Ampleford et al 2008) have also shown the development of conical shocks forming at the base and along the axis of the developed jet.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 99%
“…Lebedev 2005;Ampleford et al 2008) have also shown the development of conical shocks forming at the base and along the axis of the developed jet.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 99%
“…By employing a small, dedicated low inductance pulser to drive the xpinch, such as the one described by Mesyats et al, 19 one could couple this diagnostic to a wide range of laser plasma and pulsed power experiments. Examples include the study of conditions in hydrodynamic 20,21 and magnetically driven jets, [22][23][24] materials in WDM state, 11,12 and the structure of radiative shocks. 21,25 Additionally, the excellent spectral resolution makes it possible to improve and expand upon data previously taken of spectral opacities in highly controlled samples such as those found in Refs.…”
Section: Resultsmentioning
confidence: 99%
“…An even simpler way to explore this concept would be in a fan-shaped planar wire array in which the wires are more closely spaced at the cathode than at the anode (the 2D analog of a conical array). Like a conical wire array [58] or radial array [59], one would expect the implosion to start at the cathode where the magnetic field is higher. Multiple implosions initiating at this cathode contact point due to current restrike are often observed in radial wire arrays.…”
Section: Chapter 4 Conclusion and Future Directionsmentioning
confidence: 99%